Understanding public preferences for policing homeless individuals in the United States: results from a national survey - Burkhardt, Brett C. (Deviant behavior, 2023)
The United States has a large and growing homeless population. In the name of public order, municipalities across the country have criminalized behaviors associated with homeless people in public spaces (e.g. panhandling) and tasked police with responding to violations. What should police do in these encounters? This study reports on a nationwide survey experiment that asked US residents whether police should arrest, help, or ignore a homeless individual in several hypothetical scenarios. We estimate (1) aggregate preferences for police response, (2) the association between respondent demographics and individual preferences, and (3) the effect of experimentally manipulated identity - gender and background - of a homeless person on preferences. Results reveal that a helping response from police is generally preferred to arresting or ignoring. An arrest response received greater support from people who perceived homelessness to be a problem locally, as well as men and Republicans. The identity of the homeless individual had little effect on preferred police responses. With respect to public and policy debates about homelessness, these results suggest that there is relatively little public appetite for a heavy-handed police response, though this may not hold in areas where many people perceive homelessness to be a source of problems.